Implementasi al-Qur'an Surat al-'Alaq Ayat 1-5 dalam Pembelajaran Sains dan Teknologi - Muhtadi Muhtadi (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2020)
This study aims to describe the Implementation of al-Qur'an Surah al-‘Alaq verses 1-5 in the Study of Science and Technology. This type of research is a literature study (library research) with a qualitative descriptive approach. The data collection method uses the documentary method which is sourced from al-Qur'an at al-laAlaq verses 1-5 and several commentaries such as al-Maragi, Ibn Kathir, al-Misbah, and al-Mizan. While the data analysis method uses the Tahlily method and the Contents analysis method. The results of this study indicate that the conception of learning in the Qur'an surah al-'Alaq verses 1-5 can be interpreted as intellectual enlightenment, which can be seen from the repetition of the word iqra 'twice, thus making it a habit to continue learning continuously. While its implementation in learning Science and Technology is implied in the word Iqra '(reading), because reading here does not mean only reading a text, but reading nature, situations and conditions around us.